2007
DOI: 10.1677/joe.1.06985
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of X-linked inhibitor of apoptosis in the anterior pituitary of streptozotocin-induced diabetic rats

Abstract: Cell death is increased in the anterior pituitary of poorly controlled diabetic rats, but anti-apoptotic mechanisms are also activated. We hypothesized that specific cell types are selectively protected against diabetes-induced cell death. To determine when anti-apoptotic mechanisms are activated, streptozotocin-induced diabetic rats were killed after 1, 4, 6 and 8 weeks of evolution. Anterior pituitaries were processed for western blot analysis to determine changes in the intrinsic cell death pathway and upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…Immunohistochemistry in combination with TUNEL ( Figure 2) indicated that his cell death corresponded primarily to lactotrophs as previously demonstrated (Arroba et al, 2007). Very few TUNEL labeled cells were found in pituitaries of control rats or diabetic rats treated with ghrelin.…”
Section: Total Cell Death In the Anterior Pituitarysupporting
confidence: 79%
See 4 more Smart Citations
“…Immunohistochemistry in combination with TUNEL ( Figure 2) indicated that his cell death corresponded primarily to lactotrophs as previously demonstrated (Arroba et al, 2007). Very few TUNEL labeled cells were found in pituitaries of control rats or diabetic rats treated with ghrelin.…”
Section: Total Cell Death In the Anterior Pituitarysupporting
confidence: 79%
“…However, we previously reported that no changes in cell turnover of thyrotrophs, corticotrophs or gonadotrophs occur in poorly controlled diabetic rats (Arroba et al, 2006;Arroba et al, 2007), suggesting that changes in the synthesis and secretion by individual cells could explain the observed changes in circulating hormones. In our study pituitary TSH and ACTH content was not modified by either diabetes or ghrelin treatment to diabetic rats.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations